Application of Gamification in Learning: Its Influence on Motivation, Involvement, and Student Learning Outcomes - Prameswari, Kenyo; Novita, Iva; Pradana, Dian Arief (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
The application of gamification in education is becoming a topic that is increasingly discussed, both in the context of formal and non-formal education. The purpose of this research is to examine how the application of gamification in e-learning can increase student motivation and involvement. This research uses a qualitative approach with a literature study method that includes various previous studies on gamification in education. The results of this study show that the application of game elements in online learning can increase interactivity, strengthen the attractiveness of the subject matter, and encourage students to more actively participate in the learning process. In addition, this study also found that gamification has the potential to improve student learning outcomes by making the material more interesting and giving faster feedback. This research concludes that gamification can be an effective tool in creating a more interesting learning experience and increasing student motivation. However, further research is still needed to optimize the gamification design in various learning contexts.